Inovasi Pendidikan Dalam Mempertahankan Keputusan Orang Tua Memilih Jasa Pendidikan Sebelum Dan Sesudah Belajar dari Rumah (BDR) - Dwi Haryanti; Nurul Qomariah; Nurul Alimah (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
Conditions during the pandemic also had an impact on the decrease in the number of students attending PAUD institutions. This research is based on the belief that local cultural forms are legitimized by formal schools and formal schools can facilitate cultural reproduction. This research agrees that schools only promote and uphold values, norms, traditions and behavior that are acceptable to the local community. The methodology used in this research is a qualitative descriptive research methodology. Innovation in the marketing of education services is very important to attract public interest and attention in sending their children to these institutions. Innovation is also carried out so that the school can maintain its existence in society. The innovations carried out include the marketing of educational services. This must be done by all members involved in educational institutions consisting of teachers, employees, students, to parents or guardians so that it can run successfully. There are seven elements to focus on in carrying out these innovations, namely product, price, place, promotion, people, physical evidence, and process.